Simulating a sequential coalition formation process for the climate change problem: First come, but second served? - Michael Finus; Bianca Rundshagen; Johan Eyckmans (Fondazione Eni Enrico Mattei (FEEM), 2009)
We analyze stability of self-enforcing climate agreements based on a data set generated by the CLIMNEG world simulation model (CWSM), version 1.2. We consider two new aspects which appear important in actual treaty-making. First, we consider a sequential coalition formation process where players can make proposals which are either accepted or countered by other proposals. Second, we analyze whether a moderator, like an international organization, even without enforcement power, can improve upon globally suboptimal outcomes through coordinating actions by making recommendations that must be Pareto-improving to all parties. We discuss the conceptual difficulties of implementing our algorithm.
Keywords: C79; H87; Q54; 330; International Climate Agreements; Sequential Coalition Formation; Coordination through Moderator; Integrated Assessment Model; Algorithm for Computations